AB0535 ARE THE NEUTROPHIL/LYMPHOCYTE RATIO (NLR) AND PLATELET/LYMPHOCYTE RATIO (PLR) USEFUL TO COMPARED WITH ACUTE PHASE REACTANTS (ESR/CRP) FOR DIAGNOSIS AND PROGNOSIS OF PATIENTS WITH ACTIVE TAKAYASU'S ARTERITIS (TAK)?: AN ANALYSIS BASED ON ROC AND KAPLAN-MEIER CURVES IN A LATIN AMERICAN POPULATION. (2nd June 2020) - Torres, F.; Leon, L.; Vanegas, A.; Muñoz, C.; González, L. A.; Jaramillo, D.
Abstract : Background: The NIH criteria are the main measure to determine activity in TAK. NLR and PLR appear promising to predict disease activity (1) . TAK is one of the most frequent vasculitis in Colombia with a prevalence of 13.3%; however, in more recent years the information is sparse about TAK clinical behavior in our region, which leads to a late diagnosis. Although survival has improved with immunosuppressive treatment, relapses remain high especially in the first year of diagnosis Objectives: Compare NLR and PLR with ESR/CRP to predict TAK activity Show survival and relapse in patients with TAK followed to 7 y Methods: Retrospective cohort of 43 patients with TAK between 2011-2018 with prospective follow-up of relapses and mortality. 88% fulfilled the ACR 1990 criteria. The disease activity was determined according to NIH criteria: active disease (n=34) and inactive disease (n=9). Through bivariate analysis, we compared the clinical and radiologic characteristics between age groups (table 1 ) using the Pearson test and Wilcoxon range test. Value of p <0.05 was statistically significant. Survival and relapse analysis were performed using Kaplan-Meier plots. Sensitivity (Sn), specificity (Sp) and area under the curve (AUC) were determined for NLR, PLR, ESR and CRP by receiver-operating curves (ROC) compared to NIH criteria. Results: 41 patients were women (96%) with a median age at diagnosis of 22 y and an interval from the onset of disease to diagnosis of 12 months (IR:1-168 m). The population over 40 years had a greater comorbidities burden (54% had history of smoking and dyslipidemia) and a major interval between the onset of disease and the diagnosis (36 months vs 9.5 months). Most frequent vascular phenotypes were types V (62%) and I (16%). NLR and PLR showed poor performance to predict activity compared with CRP; NLR level of 1.74 showed to be the predictive cut-off value for active TAK (Sn: 85.3%, Sp: 37.5%, AUC = 0.563). PLR level of 112.5 was found to be the predictive cut-off value for active TAK (Sn: 76.5%, Sp: 50%, AUC = 0.517). The CRP was the most accurate biomarker (Sn: 79.4%, Sp: 75%, AUC = 0.761) while the ESR was lower to predict activity (Sn: 63.6%, Sp: 75%, AUC = 0.598) (figure 1 ). At 5 years, survival was 83% and 50% of patients had presented at least one relapse (figure 2 ) Conclusion: Our data does not support the use of NLR or PLR to differentiate relapse and remission in TAK. CRP had better diagnostic performance than ESR in the prediction of activity compared to NIH criteria. The 5-year survival in this cohort is below that reported after 1985 (reported survival: 90-96%) (2) References: [1] Pan L, et al. Platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio associated with disease activity in patients with Takayasu's arteritis: a case-control study. BMJ Open 2017; 7: e014451 [2]Schmidt J, et al. Diagnostic features, treatment, and outcomes of Takayasu arteritis in a US cohort of 126 patients, Mayo Clin Proc. 2013; 88(8): 822-30 Disclosure of Interests: None declared